On Problem of National Self-Determination of Autochthonous Peoples by Example of Southern Russia Regions (Late 1980s — Early 1990s) - M. V. Belozerova (Научный диалог)
The article considers the problem of national self-determination among the autochthonous peoples of Russia as a component of the ethnopolitical processes of the late 1980s and early 1990s. The relevance is determined by the need to study the manifested ethnic interests, inter-ethnic tension and separatist tendencies that have passed from a latent state to an open form among a number of autochthonous peoples. On the basis of comparative analysis, research of archival documents of state, departmental, personal archives and historiographical data, general trends and regional specifics of Khakas, Adygs, Shapsugs, Shors, and Teleuts are revealed. The ethno-political processes on which the ideas of national self-determination were based include the growth of ethnic consciousness, “the politicization” of ethnicity, the change of ideological paradigms, the institutional activity of national elites, the formation of national revival programs, and myth-making. The author reveals the significant commonality of myths (“search for the enemy,” “loss” of national culture and other theses) and differences based on the historical and ethnic memory of each nation. Special attention is paid to the problem of autonomy. It was seen as an emerging component in attempts to implement the idea of national self-determination. The experience of normalization of social relations was considered in the analysis of the tactics used by national elites in achieving political goals, decisions made by regional authorities, and the reaction of various segments of society.